Institutional Domain Assessment of the EAFM Approach to Snapper and Grouper Fisheries in the waters of the Sangihe Islands, North Sulawesi - dumas, Davis Wijaksana Extrada; Lasabuda, Ridwan; Manembu, Indri Shelovita; Makapedua, Daisy M.; Darwasito, Suria; Luasunaung, Alfrets; Sumilat, Deiske Adeliene; Darmono, Oktaviano P. (Jurnal Ilmiah Platax, 2024)
This research aims to assess the status of snapper and grouper fisheries management in the Sangihe Islands district using an ecosystem approach (EAFM) in the institutional domain. The research method uses observation and interview methods (questionnaires). Data collection used semi-structured interview (SSI) techniques. As a result of the assessment of 6 (six) institutional indicators, there are 2 indicators with a value of 1 (less, red flag model), namely indicators of compliance with the principles of responsible fisheries and indicators of fisheries management plans. 3 indicators each: decision-making mechanism indicators, indicators of the level of synergy of fisheries management policies & institutions, and stakeholder capacity indicators) with a value of 2 (medium, yellow model flag). Only the indicator for the completeness of the rules in fisheries management has a value of 3 (good, green model flag). The average score for the 6 indicators is 1.76 while the composite value is 58.53. This value shows that the application of the EAFM institutional domain in the management of snapper and grouper fisheries in the Sangihe Islands district is in the medium category (yellow model flag). Keywords: EAFM, Sangihe Islands, Grouper Snapper Fishery, Flag Model. Abstrak Penelitian ini bertujuan untuk menilai  status pengelolaan perikanan kakap dan kerapu di kabupaten Kepulauan Sangihe dengan pendekatan ekosistem (EAFM) pada domain kelembagaan. Metode penelitian menggunakan metode observasi dan wawancara (kuisioner). Pengumpulan data menggunakan teknik semi structured interview (SSI).  Hasil penilaian dari 6 (enam) indikator kelembagaan, ada 2 indikator yang nilai-nya 1 (kurang, flag model merah) yaitu  indikator kepatuhan terhadap prinsip-prinsip perikanan yang bertanggung jawab dan indikator rencana pengelolaan  perikanan. 3 indikator masing-masing : indikator mekanisme pengambilan  keputusan, indikator tingkat sinergisitas kebijakan & kelembagaan pengelolaan perikanan, indikator kapasitas pemangku  kepentingan) bernilai 2 (sedang, flag model kuning). Hanya indikator kelengkapan aturan main dalam  pengelolaan perikanan yang bernilai 3 (baik, flag model hijau).  Nilai skor rerata 6 indikator adalah 1,76 sedangkan  nilai komposit-nya 58,53. Nilai ini menunjukkan bahwa penerapan domain kelembagaan EAFM pada pengelolaan perikanan kakap dan kerapu di kabupaten Kepulauan Sangihe kategori sedang (flag model kuning). Kata kunci : EAFM, Kepulauan Sangihe, Perikanan Kerapu Kakap, Model Bendera